The dark triad and intimate partner violence. (15th January 2017) - Carton, Hannah; Egan, Vincent
Abstract: Psychological abuse within intimate partner violence (IPV) is poorly researched. We investigated the impact of dark triad (DT) traits and personality on psychological, physical and sexual abuse, and whether DT traits have incremental validity over general personality dimensions in the prediction of IPV expressed psychologically, physically, and sexually. IPV was measured via the Multidimensional Measure of Emotional Abuse (MMEA) and the short form of the revised Conflict Tactics Scale, version 2 (CTS2S) in a general community sample (N = 128). Correlation and regression analysis indicated that low agreeableness and psychopathy had the strongest associations and most predictive relationships with both psychological abuse and physical/sexual abuse. Low agreeableness was predictive of both the participants' and their partners' perpetration of physical/sexual abuse. A significant positive relationship was also found between high scores on the MMEA and high scores on the CTS2S. A significant positive relationship was found between participants' high psychopathy scores and perpetration of psychological abuse, but this had a smaller effect than a measure of agreeableness alone. We did not find that the DT provides incremental validity for the prediction of either psychological abuse or physical/sexual abuse over basic low Agreeableness. Highlights: Psychological abuse is more poorly researched than other aspects of intimate partner violence (IPV). Low agreeableness predicts physical abuse, but psychopathy, Machiavellianism and low openness predict psychological abuse. The DT's Machiavellianism and psychopathy may specifically capture denigration and restrictive engulfment. The addition of dark triad traits to general disposition did not improve the prediction of IPV.